Market Women of Northern Ghana within Value Chain Development - Hartmann, Anne (My University, 2017)
Trade is a widespread occupation for women in West Africa; such as petty traders that are involved with informal trade mainly. The case in Ghana is different as most of these traders are facing hostile treatment and harassment from many sides. Nevertheless, in development cooperation projects, rural economic development and development of its population is often targeted; whereas solely rural development projects have become projects to support value chains and its stakeholders. These value chains start at agricultural production, further on to processing and altering the raw product until its final condition for sale to the end consumer. The entire value chain deals with many diverse actors in rural and urban areas and also diverse areas of economies, such as micro and small enterprises, and other in private sector or public sector. Therefore, development cooperation dealing with value chain enhancement would address all actors. In Ghana, mainly production side and post-harvest management are dealt with and trade or intermediary trade is circumvented. Some projects openly state that they leave out traders from their interventions in value chains. Most prejudices of this type have derived from historical events and official institutions, also a lack of knowledge. Traders are by contrast those who are coordinating streams of goods from beyond borders to supply to domestic markets and vice versa, manage large quantities for export. The reason that women continue to work in trade is that they barely have alternatives.

Eine geringe Wertschätzung von Zwischenhändlern wie in vielen Entwicklungsländern ist auch in Ghana vorzufinden, was einerseits aus geschichtlichen Gründen aber auch aus Unwissenheit entsteht. Der Bereich der Zwischenhändler ist vorwiegend durch Frauen aus ruralen Gebieten betrieben, die Analphabeten und Autodidakten sind. Der Handel ist auf jeder Ebene organisiert, von den Kommunen über die Distriktstädte, die regionalen Hauptstädte und auch über die Grenzen des Landes hinaus. Die Händlerinnen organisieren damit den Warenfluss von den entlegenen Plätzen der Produktion oder aus dem Ausland, um es zu den Märkten mit der Nachfrage in den Ballungszentren und den großen städtischen Märkten zukommen zu lassen. Nichtsdestotrotz werden bei diversen Programmen der Entwicklungsorganisationen die Händler und vor allem Händlerinnen außen vor gelassen, die Konzentration und Aktivitäten wird auf die Produktion und teilweise auf die Handhabung nach der Ernte fokussiert. Der Wertschöpfungsketten-Ansatz verfolgt jedoch per definitionem alle Akteure in der Kette der Wertschöpfung, allein hierbei fehlen die Händler in der Umsetzung. Die Arbeit soll daher aufzeigen, welche Funktionen die Händlerinnen in den drei ausgewählten Fällen übernehmen und wie somit die Entwicklung von Wertschöpfungsketten optimiert werden und letztendlich die beteiligten Händlerinnen zu einer Verbesserung der Wertschöpfungskette beitragen können.
The Cases of Chilli, Tomato and Maize
Keywords: Stadt; Entwicklungszusammenarbeit; Arbeit; Frauenberuf; Globalisierung; 330 Wirtschaft; Ghana; Wertschöpfungskette